BANKING ON RELATIONSHIPS: A STUDY OF CUSTOMER RELATIONSHIP MANAGEMENT AT STATE BANK OF INDIA, TIRUNELVELI (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the effectiveness of Customer Relationship Management (CRM) practices at State Bank of India, Tirunelveli. The research aims to analyze the impact of CRM on customer satisfaction, loyalty, and retention. A mixed-methods approach was employed, combining surveys (n=200) and in-depth interviews (n=10) with customers and bank employees. The findings reveal significant correlations between CRM practices, customer satisfaction, and loyalty. Effective communication, personalized services, and employee responsiveness emerged as key drivers of customer relationships. However, challenges such as technological glitches, limited employee training, and inadequate feedback mechanisms were identified. The study recommends strategic interventions to enhance CRM effectiveness, including employee training programs, technology upgrades , and customer feedback mechanisms. The research contributes to the understanding of CRM in the Indian banking sector and informs policy decisions for improving customer relationships.